Femme juive de Djerba - Jourcin, Eugénie (1939)
Dans le Salon Tunisien de 1939
Keywords: Arts -- Djerba; Judaïsme -- Djerba

Libyan photograph album, 1937 (1937)
This bound album contains 98 black and white photographs taken during a trip to Libya in 1937 by an anonymous photographer. The overall technical and artistic quality of the photographs, along with how they are presented in the album suggest a photographer of above-average skill and experience. The album is inscribed: "A. B. in memory of the May days of 1937 in Tripoli in friendship G. S. W." With the exception of the first four photographs, the album consists of images that show scenes around Libya, such as the Hotel Albergo Mehari, a camel market, Tripoli Castle, a coastal oasis, a Bedouin village, markets and bazaars. Prominent locations shown include, Tripoli, Sabratha, Leptis Magna, Zliten, and Yefren. Additionally, photographs of people, including children, locals, officials, and soldiers can be found throughout. The first four photographs in the album appear to be scenes just prior to leaving Italy, particularly the fourth photograph, which shows the skyline of Rome and has the caption, "Departing Rome April 30." All of the writing in this album is either in German or Italian. Translation and interpretation of these languages was performed using translation tools only.
Keywords: Récits de voyage -- Djebel Nefousa

Visit of the Sultan of Muscat and Oman to England - Sport & General Press Agency; London News Agency (1938)
Genre/Subject Matter: Two official photographs of the Sultan of Muscat and Oman, Āl Sa‘īd, Sa‘īd ibn Taymūr, during his visit to England in 1938. The photographs were taken on April 1 and April 4 respectively. The visit was part of the Sultan’s world tour 1937–38. Each photograph was taken by a separate press agency.
Keywords: Récits de voyage -- Oman

FTG7 A Nalut hotel - Dudovich, Marcello (1930)
Keywords: Récits de voyage -- Djebel Nefousa